Chapter 2 Gender and post-election intraparliamentary volatility in East Central Europe The cases of the Czech, Lithuanian, and Polish parliaments - Żukiewicz, Przemysław (Taylor & Francis, 2022)
Gender, Politics, Elections, Democracy, LGBTQ